The Use of Instagram for Students' Writing Skills - Nida Uswatun Hasanah; Anita Dewi Ekawati (JPG: Jurnal Pendidikan Guru, 2024)
One of the most popular social media sites among young people is Instagram. With its many features, Instagram can be used as a fun and non-monotonous writing lesson. This study examined the students’ perceptions of using Instagram for their writing skills. In this study, the descriptive quantitative method was used. This study included 150 participants from students’ universities, and questionnaires distributed over WhatsApp were used to collect research data. There were 10 items and the participants were expected to choose the most appropriate option from the 4-level Likert Scale labeled by: Strongly Disagree, Disagree, Agree, and Strongly Agree. According to the study’s findings, Instagram is an effective tool for improving learners’ vocabulary range and grammatical accuracy. Learners also gain better ideas prior to writing tasks and develop their own writing style. If used and supervised properly, Instagram could be an effective pedagogical tool for learning a second language.